Great economists before Keynes : an introduction to the lives & works of one hundred great economist of the past/s - Blaug, Mark. (Brighton, Sussex : Wheatsheaf Books : Distributed by Harvester Press, 1986)
Great economists before Keynes is a companion volume to the acclaimed Great Economists since Keynes. It presents 100 stylish and authoritative intellectual biographies together with portraits of great economist of the past..
Includes bibliographical references and indexes.
ijb, 14/11/2018
Loans
Keywords: Economists